2020
DOI: 10.1158/1078-0432.ccr-20-1960
|View full text |Cite
|
Sign up to set email alerts
|

Acute Statin Treatment Improves Antibody Accumulation in EGFR- and PSMA-Expressing Tumors

Abstract: ◥Purpose: Statins are cholesterol-depleting drugs used to treat patients with hypercholesterolemia. Preclinically, statins disrupt trafficking of receptors present at the cell membrane. Membrane receptors, defined as tumor biomarkers and therapeutic targets, are often internalized by an endocytic pathway. Indeed, receptor endocytosis and recycling are dynamic mechanisms that often affect receptor density at the cell surface. In therapies using monoclonal antibodies (mAb), a downregulation in receptor density a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 64 publications
1
34
0
1
Order By: Relevance
“…This is consistent with previous preclinical studies temporally increasing cell-surface receptors to potentiate TDM1 therapy [58]. Controlled use of lovastatin, at doses lower than the maximum human dose, produce a temporal decrease in CAV1 protein levels [35]. Compared with lipophilic lovastatin, hydrophilic statins are less able to cross cancer cell membranes as they require active transport to enter cells [59].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This is consistent with previous preclinical studies temporally increasing cell-surface receptors to potentiate TDM1 therapy [58]. Controlled use of lovastatin, at doses lower than the maximum human dose, produce a temporal decrease in CAV1 protein levels [35]. Compared with lipophilic lovastatin, hydrophilic statins are less able to cross cancer cell membranes as they require active transport to enter cells [59].…”
Section: Discussionsupporting
confidence: 89%
“…Importantly, the lipophilic prodrug lovastatin depletes tumoral CAV1 in ways that improve antibody binding to tumors [22,34,35]. Similarly, lovastatin enhances TDM1 uptake in CAV1high PDXs, confirming an association between the loss of CAV1 and ADC uptake.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Recent evidence suggests that simvastatin may enhance the sensitivity of C26 mouse colon cancer cells to 5-FU treatment [ 301 ]. Pereira et al found that statins temporarily modulated the epidermal growth factor receptor (EGFR) and prostate specific membrane antigen (PSMA) on the surface of tumor cells, which enhanced the tumor-binding avidity of the monoclonal antibodies panitumumab, cetuximab and huJ591, thereby synergizing with the antitumor effects of these agents [ 302 ]. It has also been reported that lovastatin enhanced the sensitivity of gallbladder cancer to cisplatin [ 303 ].…”
Section: Maximizing Efficacy and Addressing Shortcomings Of Conventional Cancer Therapymentioning
confidence: 99%